A Systematic Review on Real Time Video Compression and Enhancing Quality Using Fuzzy Logic - Srivastava, Upendra Kumar; Prakash, Navin (International Journal of Computer Sciences and Engineering, 2025)
This paper provides the critical reviews on Real time Video Compression and Efficient use of Fuzzy Logic Techniques used in Video Compression and Quality Enhancement. Since the Internet is highly heterogeneous environment video codec needs to be able to generate bit streams that are highly scalable in terms of bandwidth and processing requirements looking all these problems this research paper explores the possibility of better compression ratio in real time and quality enhancement by efficient use of fuzzy logic . The first section of this paper tells the overview of the real time video compression .The second section of this paper describes the related work which has been done in the past regarding real time video compression it consists a Table-1 in reference of the time line of real time video compression and Table -2 about the differences between H.265 and H.264 .The third section of this paper consists a Table-3 which represents about the research time line using fuzzy logic in video compression .The fourth section of this paper consists a Table-4 which represents the research time line of real time video compression. Finally the conclusion of this paper is an overview on past, present and future trends in Video Compression Technologies, review of the improvements and development in video encoding over the last two decades with future possibilities